THEORETICAL AND METHODOLOGICAL PECULIARITIES OF THE DEVELOPMENT PROCESS OF DYNAMIC COMPETITIVE STRATEGIES FOR BAKERY ENTERPRISES - Д. В. Завертаний (Ринкова економіка: сучасна теорія і практика управління)
In modern conditions, the role and importance of the study of the methodology of the formation and evaluation of a dynamic competitive strategy of bakery enterprises is increasing. The analysis of trends in the development of the Ukrainian bakery industry, factors of influence, causal relationships and the consequences of the changes that are taking place gives rise to a clear idea of its state of affairs, as well as to determine the priority directions of further development of the methodology of forming a competitive strategy. A leading role in shaping the strategic planning methodology is played by a system of methodological principles that defines qualitative parameters of strategic planning, as well as substantiates new scientific approaches and methods used in the formation of a dynamic competitive strategy. Today there is no single unambiguous approach to the definition of the methodology of the formation and evaluation of the effectiveness of dynamic competitive strategies of the bakery industry. Scientists express different views on the subject, methods and objectives of methodological research. The methodological feature of the formation of dynamic competitive strategies for the enterprises of the bakery industry is that this activity is largely experimental because of its specific nature, since the development of a dynamic competitive strategy is based on the data that can be obtained in conducting not just the study of any factors, but it is the study, that is, the acquisition of completely new knowledge about the internal and external environment of the organization. The strategist, before embarking on the creative formation of a dynamic competitive strategy, must obtain new scientific knowledge through special methods of economic research. Thus, scientific research in the formation of dynamic competitive strategies of the enterprises of the bakery industry in each cycle makes movement from the empirical base to the theory and from theory to practice. The completion of this cycle is simultaneously the beginning of a new cycle, which provides a continuous process of increasing the knowledge necessary for the formation of dynamic competitive strategies. The peculiarity of the formation of dynamic competitive strategies lies not only in the fact that this activity is largely due to its specificity, the experimental nature, but also that the scientific research in the formation of dynamic competitive strategies in each cycle makes the movement from the empirical basis to the theory and from theory to practice. Thus, the strategic process of baking plants cannot be considered without defining the strategy concept, as well as without analyzing the types of strategic processes. The key to the effectiveness of the strategic process is the interaction of internal and external environments, which in turn include operational and intelligence processes.